MODIFIKASI ALAT PEMBELAJARAN UNTUK MENINGKATKAN KETERAMPILAN PASSING BAWAH PADA PERMAINAN BOLA VOLI MINI DI SDN JEJANGKIT TIMUR (1) - sudarsinah (Program Studi PGSD STKIP PGRI Banjarmasin, 2021)
The purpose of universal physical education is to develop cognitive, effective and psychomotor abilities of students. The current reality is that learning physical education, sports and health at SDN Jejangkit Timur has limited tools and facilities in learning activities, besides that learning is only carried out in a simple way using old patterns (lectures) so that the learning carried out is not achieved optimally. The purpose of the study was to improve the skills of passing down in mini volleyball games for fifth graders at SDN Jejangkit Timur. This type of research uses CAR. The research method used is descriptive quantitative method with data collection through initial evaluation and final evaluation of students' skills in passing down a mini volleyball game. The results of the study showed that the learning activity of passing under class V students in the 2018/2019 academic year with the results of calculations in data analysis through statistical testing obtained the results: to = 4.47 > ttable (0.05) of 1.68 so it can be stated that there is a significant difference between the results of the initial skill evaluation with the results of the final bottom passing skill evaluation. The conclusions of this study indicate that through this approach learning can improve the skills of students at SDN Jejangkit Timur in passing down a mini volleyball game after using modified tools in learning.